2021
DOI: 10.1088/1757-899x/1011/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Application of feed forward neural network model to predict the limiting current of tin magneto electrodeposition

Abstract: Predicting the value of Tin Magneto electrodeposition (MED) is very important since the optimum mass transport occurred at the limiting current. The MED limiting current able to detect using electroanalytical chemistry, but this method is expensive; it needs some method, which able to predict the limiting current of tin MED. However, predicting the limiting current under magnetic field effect is more complicated due to the highly nonlinear characteristic and complicated of its multiple inputs single-output (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It was found that using the feed forward neural network the thickness of the fouling layer was predicted with an accuracy of 0.983. In [63] a feed forward neural network is used to predict the limiting current of tin magneto electrodeposition. It is known from literature that the limiting current of tin magneto electrodeposition determines the efficiency of transforming one distribution of mass into another.…”
Section: Feed Forward Neural Networkmentioning
confidence: 99%
“…It was found that using the feed forward neural network the thickness of the fouling layer was predicted with an accuracy of 0.983. In [63] a feed forward neural network is used to predict the limiting current of tin magneto electrodeposition. It is known from literature that the limiting current of tin magneto electrodeposition determines the efficiency of transforming one distribution of mass into another.…”
Section: Feed Forward Neural Networkmentioning
confidence: 99%